2021
DOI: 10.1007/s00425-020-03562-4
|View full text |Cite
|
Sign up to set email alerts
|

Avena fatua caryopsis dormancy release is associated with changes in KAR1 and ABA sensitivity as well as with ABA reduction in coleorhiza and radicle

Abstract: Main conclusion The dormancy release in Avena fatua caryopses was associated with a reduction in the ABA content in embryos, coleorhiza and radicle. The coleorhiza proved more sensitive to KAR1 and less sensitive to ABA than the radicle. The inability of dormant caryopses and ABA-treated non-dormant caryopses to complete germination is related to inhibition and delayed of cell-cycle activation, respectively. Abstract As freshly harvested Avena fatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it was observed that ABA catabolism is rapid enough to play an important role in the regulation of ABA accumulation as studied in the maize plants ( Ren et al, 2007 ). Again in the case of cereals, investigation in barley coleorhiza proved that the ABA 8 ′- hydroxylase gene plays a significant role in seed dormancy release ( Kępczyński et al, 2021 ).…”
Section: Role Of Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…Furthermore, it was observed that ABA catabolism is rapid enough to play an important role in the regulation of ABA accumulation as studied in the maize plants ( Ren et al, 2007 ). Again in the case of cereals, investigation in barley coleorhiza proved that the ABA 8 ′- hydroxylase gene plays a significant role in seed dormancy release ( Kępczyński et al, 2021 ).…”
Section: Role Of Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…Recently, it has been also postulated that that the coleorhiza-enforced dormancy in caryopses of A. fatua (Holloway et al 2020 ). After-ripening, also KAR 1 decreased the ABA content in the coleorhiza before germination was completed (Kępczyński et al 2021 ). ABA inhibited radicle emergence after-ripened caryopses A. fatua more strongly than coleorhiza emergence (Holloway et al 2020 ; Kępczyński et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NO, an uncharged, gaseous lipophilic free radical can regulate seed dormancy and germination in several dicot plant species (Bethke et al 2007 ; Arc et al 2013 ; Matilla et al 2015 ; Singorelli and Considine 2018; Kumar et al 2021 ). Various NO donors, such as sodium nitroprusside (SNP), S-nitroso- N -acetylpenicillamine (SNAP), S-nitrosoglutathione (GSNO) or acidified KNO 2 were found to promote dormancy release in apple (Gniazdowska et al 2007 ), Arabidopsis (Bethke et al 2004 ), lettuce (Belgini and Lamattina 2000 ) and redroot pigweed (Kępczyński and Sznigir 2014 ) seeds. Thus, different NO donors have often been used in experiments with seeds of various plant species, aimed at elucidating the role of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the following methods have been identified as being effective techniques for overcoming dormancy in wild oat seeds. Methods that overcome PD dormancy include altering temperature and photoperiod regimes for germination (Somody et al 1984), adjusting the osmotic potential of the seed and light conditions (Boyd and Van Acker 2004), exposing the seed to ammonia gas (Cairns and De Villiers 1986), presoaking the seed in potassium nitrate solution (Hilton 1985), application of sodium hypochlorite and hydrogen peroxide in combination with GA; (Hsiao and Quick 1984), application of a variety of soluble sugars and GA (Foley 1992), as well as other reagents (Beckie et al 2012;Kępczyński et al 2021;Saini et al 1986). Methods that overcome PY dormancy include exposure of the seed to high-pressure gas (Hoffmann 1961), manual removal of lemma and palea (Kommedahl et al 1958), seed dipping in diluted sulfuric acid, and cold stratification treatment (Shahvand et al 2015).…”
Section: Introductionmentioning
confidence: 99%